The origins of catatonia - systematic review of historical texts between 1800 and 1900 - Hirjak, Dusan; Foucher, Jack R.; Ams, Miriam; Jeanjean, Ludovic C.; Kubera, Katharina Maria; Wolf, Robert Christian; Northoff, Georg (Schizophrenia research, 2024)
Since January 1st 2022, catatonia is (again) recognized as an independent diagnostic entity in the 11th revision of the International Classification of Diseases (ICD-11). This is a relevant time to systematically review how the concept of catatonia has evolved within the 19th century and how this concept changed under the influence of a wide variety of events in the history of psychiatry. Here, we systematically reviewed historical and modern German and English texts focusing on catatonic phenomena, published from 1800 to 1900. We searched five different electronical databases (https://archive.org, www.hathitrust.org, www.books.google.de, https://link.springer.com and PubMed) and closely reviewed 60 historical texts on catatonic symptoms. Three main findings emerged: First, catatonic phenomena and their underlying mechanisms were studied decades before Karl Ludwig Kahlbaum's catatonia concept of 1874. Second, Kahlbaum not only introduced catatonia, but, more generally, also called for a new classification of psychiatric disorders based on a comprehensive analysis of the entire clinical picture, including the dynamic course and cross-sectional symptomatology. Third, the literature review shows that between 1800 and 1900 catatonic phenomena were viewed to be ‘located’ right at the interface of motor and psychological symptoms with the respective pathophysiological mechanisms being discussed. In conclusion, catatonia can truly be considered one of the most exciting and controversial entity in both past and present psychiatry and neurology, as it occupies a unique position in the border territory between organic, psychotic and psychogenic illnesses.
Online verfügbar: 14. Juni 2022, Artikelversion: 18. Dezember 2023
Gesehen am 06.05.2024